Initiating tocilizumab, with or without methotrexate, compared with starting methotrexate with prednisone within step-up treatment strategies in early rheumatoid arthritis: an indirect comparison of effectiveness and safety of the U-Act-Early and CAMERA-II treat-to-target trials. Issue 10 (13th June 2019) - Verhoeven, Maxime MA; de Hair, Marjolein JH; Tekstra, Janneke; Bijlsma, Johannes WJ; van Laar, Jacob M; Pethoe-Schramm, Attila; Borm, Michelle EA; ter Borg, Evert-Jan; Linn-Rasker, Suzanne P; Teitsma, Xavier M; Lafeber, Floris PJG; Jacobs, Johannes WG; et al.
Abstract : Objectives: Methotrexate (MTX), often combined with low moderately dosed prednisone, is still the cornerstone of initial treatment for early rheumatoid arthritis (RA). It is not known how this strategy compares with initial treatment with a biological. We therefore compared the effectiveness of tocilizumab (TCZ), or TCZ plus MTX (TCZ+MTX) with MTX plus 10 mg prednisone (MTX+pred), all initiated within a treat-to-target treatment strategy in early RA. Methods: Using individual patient data of two trials, we indirectly compared tight-controlled treat-to-target strategies initiating TCZ (n=103), TCZ+MTX (n=106) or MTX+pred (n=117), using initiation of MTX (n=227) as reference. Primary outcome was Disease Activity Score assessing 28 joints (DAS28) over 24 months. To assess the influence of acute phase reactants (APRs), a disease activity composite outcome score without APR (ie, modification of the Clinical Disease Activity Index (m-CDAI)) was analysed. Secondary outcomes were remission (several definitions), physical function and radiographic progression. Multilevel models were used to account for clustering within trials and patients over time, correcting for relevant confounders. Results: DAS28 over 24 months was lower for TCZ+MTX than for MTX+Pred (mean difference: −0.62 (95% CI −1.14 to −0.10)). Remission was more often achieved in TCZ+MTX and in TCZ versus MTX+pred (p=0.02/0.05, respectively). Excluding APRs from the disease activity outcome score, TCZ-based strategies showed a slightly higher m-CDAI compared with MTX+pred, but this was not statistically significant. Other outcomes were also not statistically significantly different between the strategies. Conclusions: In patients with early RA, although TCZ-based strategies resulted in better DAS28 and remission rates compared with MTX+pred, at least part of these effects may be due to a specific effect of TCZ on APRs.